Evaluation of innate and adaptive immunity contributing to the antitumor effects of PD1 blockade in an orthotopic murine model of pancreatic cancer. (2nd June 2016) - D'Alincourt Salazar, Marcela; Manuel, Edwin R.; Tsai, Weimin; D'Apuzzo, Massimo; Goldstein, Leanne; Blazar, Bruce R.; Diamond, Don J.
ABSTRACT: Despite the clinical success of anti-PD1 antibody (α-PD1) therapy, the immune mechanisms contributing to the antineoplastic response remain unclear. Here, we describe novel aspects of the immune response involved in α-PD1-induced antitumor effects using an orthotopic K ras G12D /p53 R172H /Pdx1-Cre (KPC) model of pancreatic ductal adenocarcinoma (PDA). We found that positive therapeutic outcome involved both the innate and adaptive arms of the immune system. Adoptive transfer of total splenocytes after short-term (3 d) but not long-term (28 d) PD1 blockade significantly extended survival of non-treated tumor-bearing recipient mice. This protective effect appeared to be mostly mediated by T cells, as adoptive transfer of purified natural killer (NK) cells and/or granulocyte receptor 1 (Gr1) + cells or splenocytes depleted of Gr1 + cells and NK cells did not exhibit transferrable antitumor activity following short-term PD1 blockade. Nevertheless, splenic and tumor-derived CD11b + Gr1 + cells and NK cells showed significant persistence of α-PD1 bound to these cells in the treated primary recipient mice. We observed that short-term inhibition of PD1 signaling modulated the profiles of multifunctional cytokines in the tumor immune-infiltrate, including downregulation of vascular endothelial growth factor A (VEGF-A). Altogether, the data suggest that systemic blockade of PD1 results in rapid modulation of antitumor immunity that differs in the tumor microenvironment (TME) when compared to the spleen. These results demonstrate a key role for early immune-mediated events in controlling tumor progression in response to α-PD1 treatment and warrant further investigation into the mechanisms governing responses to the therapy at the innate-adaptive immune interface.